Assessment of Patient's Knowledge about Avoidance of Recurrent Urolithiasis - Jumah Abdulrida; Haleema Kadhim (Kufa Journal for Nursing Sciences)
Objectives : To assess the patient's knowledge about avoidance of recurrent Urolithiasis, and to identify the relationship between some variables (age, gender, level of education) and patient's knowledge.